Introduction to quantitative analysis of linguistic survey data an atlas by the numbers - Kretzschmar, William A., Jr.; Schneider, Edgar W. (Edgar Werner), 1954-; Sage eBooks (Thousand Oaks, Calif. : SAGE, 1996)
The chapters in this innovative book introduce the quantitative analysis of linguistic survey data with specific reference to the Linguistic Atlas of the Middle and South Atlantic States (LAMSAS). The topics covered include the relation of sociolinguistics to the original conception of LAMSAS, the adaptation of LAMSAS to the needs of computerization and the research methods envisioned, the mechanics involved in computerizing LAMSAS, and much more.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Dialectology -- Statistical methods; Dialectology -- Data processing; English language -- Dialects -- Middle Atlantic States -- Data processing; English language -- Dialects -- Southern States -- Data processing; English language -- Middle Atlantic States -- Data processing; English language -- Southern States -- Data processing; Middle Atlantic States -- Languages -- Data processing; Southern States -- Languages -- Data processing; Electronic books